Diagnostic Role and Methods of Detection of Cardiac Troponins: An Opinion from Historical and Current Points of View - Michailovich Chaulin, Aleksey (Current Cardiology Reviews, 2023)
The laboratory methods for the determination of cardiac troponins (cTnI, cTnT) used nowadays are extremely diverse, which has a significant impact on our understanding of the biology and diagnostic the value of cTnI and cTnT as biomarkers. The main classification of methods for the determination of cTnI and cTnT is based on the sensitivity of the immunoassay. Low- and moderately sensitive detection methods are known to be relatively less sensitive, which leads to a relatively late confirmation of cardiomyocyte death. Due to the new highly sensitive methods used to determine cTnI and cTnT, designated as a highly or ultrasensitive immunoassays (hs-TnT and hs-TnT), we received new, revised data about the biology of cardiac troponin molecules. In particular, it became clear that they can be considered products of normal myocardium metabolism since hs-TnT and hs-TnT are detected in almost all healthy patients. It also turned out that hs-TnT and hs-TnT differ by gender (in men, troponin concentration in the blood is higher than in women), age (in elderly patients, the levels of troponins are higher than in young ones) and circadian cycles (morning concentrations of troponins are higher than in the evening). A large variety of methods for determining cTnI and cTnT, differing in their diagnostic capabilities, creates the need for tests to perform an unbiased assessment of the analytical characteristics of each method. This review focuses on the most pressing issues related to the discussion of the biological characteristics of cardiac troponin and the analytical characteristics of troponin immunoassays from a historical and contemporary point of view.
Keywords: troponin I